PENDAMPINGAN BELAJAR MATEMATIKA DAN PEMANFAATAN ALAT PERAGA DI KOMUNITAS ANAK MAKANAN BABI KOLHUA - Michael Fernandez; Aloysius Joakim Fernandez (Universitas katolik Musi Charitas, 2018)
Mathematics subject is always considered as one of the most difficult subjects. To overcome this difficulty in learning mathematics, school age students must be given a variety of mentoring and mathematical learning approaches. The Pork Food Community, is a community of school-age children whose daily lives have to divide their time for school, after which they search for 'pork food', and time to study at home. Another problem is that the economic condition of parents causes these children to be unable to get private lessons. Therefore mentoring for learning mathematics, in mentoring was also given to learn mathematics with integer counting operation props. So that it can increase interest in learning mathematics.